Creating entrepreneurship through social innovation: The case of I-Box Create - Carolina Senent-Bailach; Andrea Rey-Martí (Contemporary Economics, 2017)
Social innovation enriches cities and drives their development by enabling improvements to products, services, processes, and methods. In this article, we define the concept of social innovation and explain which factors are essential to the social innovation process. We also examine the stages of this process. To do so, we present findings from a case study of I-Box Create, a socially innovative company based in the Region of Valencia (Spain). We thus put into practice the theory that is presented in the literature. Finally, we present the conclusions and practical implications of the study.
Keywords: O35; L31; M13; 330; Social innovation; Case study; Social entrepreneurship; Region of Valencia; I-Box Create; Startup